CONTEXTUALIZING SPEECH ACTS PERFORMED BY SUNDAY SCHOOL CHILDREN AT ST. FRANSISKUS ASSISI CHURCH MEDAN - VITALIA HANAKO MURNI SIMANJUNTAK (UIBU, 2022)
Although several types of research on speech acts have been widely conducted in many communication activities in Indonesia, studies on speech acts in religious communication inside the church, particularly those involving instructors and Sunday school pupils, are still uncovered. The study deals with the analysis of Speech Acts of The Sunday School Children of St. Fransiskus Assisi Church Medan. The purpose of this study is to describe the presentation of Illocutionary acts and their types which are dominantly used by the Sunday School Teachers. Utilizing Searle’s theory, the research was conducted by using a Qualitative Descriptive Research Method by using a case study research design. The participants of the study were 3 Sunday school teachers and 75 Sunday school children drawn by using purposive sampling technique with a total data of 200 utterances collected using recording and observations, which were analyzed in the study using qualitative data analysis technique to find out the pattern of speech acts. The study shows that there are five types of illocutionary acts used by Sunday school teachers: directives, assertive, expressive, commissions, and declarative. The most dominant type of speech acts in communication presentations were directives reaching up to 68,91%, whereas the least to occur was the declarative type (0.51%). The results of this study restate that the communication aspects that should be practiced in Sunday schools’ children should emphasize persuasive expressions to persuade Sunday school children to be more active in worshiping and listening to God's word as well as to grow their faith.